2020
DOI: 10.20517/2394-5079.2020.49
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis as a risk factor for the development of hepatocellular carcinoma

Abstract: How to cite this article: Alqahtani SA, Colombo M. Viral hepatitis as a risk factor for the development of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 150 publications
(193 reference statements)
0
15
0
Order By: Relevance
“…This study showed that donors with the O blood group, particularly those with O RhD +ve blood group, were more at risk of developing TTIs, whereas donors with the AB blood group, the AB RhD −ve blood group, in particular, were at the lowest risk of developing TTIs. According to a study by Farwa Sijjeel et al, donors with blood group O were found to be highly contaminated with TTIs [ 13 ]. On the other hand, donors with blood group A were shown to be at a higher risk of developing HBV and HIV, while those with group O showed no significant association with TTIs in research conducted in Peshawar, Pakistan [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that donors with the O blood group, particularly those with O RhD +ve blood group, were more at risk of developing TTIs, whereas donors with the AB blood group, the AB RhD −ve blood group, in particular, were at the lowest risk of developing TTIs. According to a study by Farwa Sijjeel et al, donors with blood group O were found to be highly contaminated with TTIs [ 13 ]. On the other hand, donors with blood group A were shown to be at a higher risk of developing HBV and HIV, while those with group O showed no significant association with TTIs in research conducted in Peshawar, Pakistan [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a chronic hepatitis B infection have a higher risk of developing liver cirrhosis and cancer, as well as a variety of other disorders. This infection is extremely contagious [ 13 ]. Due to their similar viral transmission paths, HCV and HBV infections are well-known among HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Viral hepatitis is one of the major contributing factors to cirrhosis and liver cancer 30 . Fungal diversity and composition were studied, via culture‐independent and culture‐dependent methods, in faecal samples from patients with chronic HBV infection with and without cirrhosis, and healthy volunteers.…”
Section: Associations Of Fungi With the Development And Progression O...mentioning
confidence: 99%
“…Data analysis was based on group-consensus analysis method 20 . The reference result was the result with 80% similar level among participated laboratories in the same method 21 . In case of similar level below 80% or group method testing below 10 participated labs using, the reference result would be from EQA provider.…”
Section: Discussionmentioning
confidence: 99%